EFEKTIVITAS SISTEM APLIKASI SATKER (SAS) DALAM PENGELOLAAN KEUANGAN PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI BALI - Harmaeni, I Gst Ag Ayu Intan; Yudartha, I Putu Dharmanu; Winaya, I Ketut (CITIZEN CHARTER; Vol 3 No 2 (2023): Administrasi Publik 2023, 2024)
The development of information technology, especially in the financial management of the public sector, requires a data processing system that produces accurate information using the SAS application (Satker Application System) and helps to make work units more effective and efficient. The purpose of this study is to determine the effectiveness of implementing SAS in financial management in the regional office of the Ministry of Religious Affairs in Bali Province. This study uses descriptive qualitative research with data collection techniques in the form of observation, documentation and in-depth interviews with informants. Measuring the effectiveness of information systems uses DeLone and Mclean's theory, which consists of system quality, information quality, service quality, user intention, user satisfaction, and net profit. The results of this study indicate that the effectiveness of SAS implementation at the Regional Office of the Ministry of Religion of Bali Province in managing public finances is not optimal. This is because there are still deficiencies found in the system so that it is necessary to increase the system and operators in the SAS application. This can be seen from errors still being found in the system when logging in and data input errors still being made by operators.